Research involvement among undergraduate medical students in Bangladesh: a multicenter cross-sectional study - Mohammad Jahid Hasan; Salwa Islam; Hasnat Sujon; Fahmida Islam Chowdhury; Muna Islam; Mostak Ahmed; Mahbuba Shabnam; Mahbub Mayukh Rishad; Mohammad Nurunnabi; Md Marufur Rahman; Jannatul Fardous; Mir Susmita Zaman; et al. (BMC Medical Education)
Abstract Background The involvement of undergraduate medical students in research is pivotal for the advancement of evidence-based clinical practice. This study aimed to assess the extent of research involvement and the factors influencing it among undergraduate medical students in Bangladesh. Methods A multi-center cross-sectional study involving 2864 medical students from both public and private medical colleges was conducted between June and December 2023. Data on demographics, research involvement, participation in research training, future career aspirations in research, and obstacles encountered by students were collected. Statistical analyses were performed using SPSS 25. Results The mean age of the students was 21.8 ± 1.8 (SD) years, with the majority being female (61.8%). Overall, 21.5% (n = 617) were actively participating in research beyond academic activities. Approximately 7% (n = 205) had undergone formal research training, and 6.5% (n = 187) had experience in publications in peer-reviewed journals as first authors or coauthors. A total of 45.5% of the students faced multiple challenges during participating in research, with the two most difficult tasks being designing a study (26.7%) and data collection and recruitment of study participants (19.6%). Almost half of the students (47.2%, n = 1352) showed an interest in pursuing a research career in the near future. The primary barriers preventing students from choosing a future research career were insufficient mentorship (16.3%), the perception of a lengthy career path (17.2%), and limited funding opportunities (15.9%). Factors that significantly encouraged research involvement included being male (adjusted odds ratio [aOR] 1.5, 95% CI: 1.2–1.8), studying in the senior academic phase (aOR 3.9, 95% CI: 2.7–5.6), previous education from an English-medium educational institute (aOR 1.8, 95% CI: 1.2–2.2), and encouragement from faculty (aOR 1.4, 95% CI: 1.1–1.7). Conclusion The proportion of research participation among the students was relatively low. To promote research engagement among undergraduate medical students in Bangladesh, comprehensive policy formulation and strong commitment at the highest levels are essential. Integrating national research policy into the curriculum could serve as a strategic measure for achieving this objective.